Strengths and Weaknesses in Applying Servant Leadership in Schools in the Age of Independence Learning: A Literature Review - Ramdini, Henri; Nurdin, Diding; Suryana, Asep; Kadarsah, Deni (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
This research aims to conduct an analysis of the strengths and weaknesses that arise in implementing servant leadership in schools in the era of Kurikulum Merdeka (KM). Using a qualitative approach, literature study is the method used in this research. The data source in this research is peer-reviewed journal articles that have been published by accredited journal publishers from the Scopus and Google Scholar databases. The article search process begins with exploring articles from the Scopus and Google Scholar portals. We visit official article pages to strictly select trusted sources from the start. By establishing exclusion and inclusion criteria, we selected 79 articles and determined 11 articles as primary data sources. The results of this research show that the application of servant leadership in schools can provide 12 positive impacts that are beneficial for teachers, education staff, students, and the performance of school organizations which can be accepted as an element of strength in efforts to achieve school goals. However, there is a threat of chaos in the school organization when the implementation of servant leadership is not supported by adequate detailed guidelines. We recommend that education policymakers design and establish detailed guidelines regarding servant leadership in schools.